Consumer Buying Behavior for Nondurable Goods - Manandhar, Binita (Management Dynamics, 2019)
The aims of the study is to analyse consumer buying behavior for non-durable goods. Descriptive and causal research design was used. Structure questionnaires were administered to gather responses. Measurement instrument is based on five point Likert scale. The study confirmed perceived quality influence on consumer purchase decision. There were no significance differences on consumer purchase decision regarding age and income level of respondents.